(untitled) (ACME, 2025)
This brief note discusses the previous interpretations proposed for the list of dishes in Ar. fr. 264 K.-A.. By examining the sources provided by the scholars (Suet. Nero 25; Eratosth. FGrHist 14; Plut. Glor. Ath. 6, 349a 10-13), it is argued that the fragment is neither centered on an unspecified ritual nor on the habit of φυλλοβολία. A figured interpretation of the fragment in a meta-literary sense is eventually recommended.